Religion on the rocks : Hohokam rock art, ritual practice, and social transformation - Wright, Aaron M. (Aaron Michael) (The University of Utah Press, 2014)
"Intrigued by the petroglyphs and pictographs of the American Southwest, people commonly ask what these symbols mean. Religion on the Rocks redirects our attention to the equally important matter of what compelled ancient farmers to craft rock art in the first place. To answer this, Aaron Wright presents a case study from Arizona's South Mountains, an area once flanked by several densely populated Hohokam villages. Synthesizing results from recent archaeological surveys, he explores how the mountains' petroglyphs were woven into the broader cultural landscape and argues that the petroglyphs are relics of a bygone ritual system in which people vied for prestige and power by controlling religious knowledge. The features and strategic placement of the rock art suggest this dimension of Hohokam ritual was participatory and prominent in Hohokam life. Around AD 1100, however, petroglyph creation, along with other ritual practices began to wane, denoting a broad transformation of the Hohokam social world. Wright's examination of the South Mountains petroglyphs offers a novel narrative of how Hohokam villagers negotiated a concentration of politico-religious authority around platform mounds. Readers will come away with a fuller understanding of the Hohokam legacy and a greater appreciation for rock art's value to anthropology"--